An International History of Coalminers’ Actions to Voice Resistance to the Appropriation of their Safety and Health, 1870-1925 - Walters, David; Quinlan, Michael (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2020)
This paper seeks to explore the history of miners’ struggles to represent their interests in health and safety in coalmines in a range of countries in the period between 1870 and 1925. It has two objectives, the first objective being to examine these struggles both in terms of what determined them and how effective they were. The second objective is to assess the significance of these struggles for current understandings of representative participation in Occupational Health and Safety (OHS). Starting with late 19th century Australia, the research method involved search, retrieval and analysis of historical sources including newspaper accounts, recorded testimony to Commissions of Inquiry into mining incidents and disasters, records of the debates of the legislature on relevant regulatory reforms and records of trade union meetings, as well as the accounts of contemporary observers and published analysis.Extending its inquiry to other countries, including the United Kingdom, Canada, France and Belgium, the methods used for these countries were less focused on newspaper accounts and more reliant on the analysis of published historical records of national and international trade union congresses, and those of the legislatures of these countries, as well as theses and accounts in the research literature. In combination, these sources corroborate one another and provide rich qualitative data, the analysis of which has achieved both research objectives.As well as filling an important gap in the literature on the development of worker involvement in OHS, this paper shows that coalminers’ struggles and strategies for workers to have a say in their health and safety, and the contexts that shaped them are both instructive and important in understanding current experiences.